Strategies to achieve controlled auto-ignition (CAI) combustion: A review - Ibham Veza; Indra C. Setiawan; La Ode M. Firman; Handi Handi; Ayu Amanah; Mega T. Kurnia; Permana A. Paristiawan; Muhammad Idris; Ahmed Sule; Anthony C. Opia (Universitas Muhammadiyah Magelang, 2023)
Conventional gasoline engines suffer from low performance and NOx emissions. Controlled auto-ignition (CAI), sometimes referred to as homogeneous charge compression ignition (HCCI), is a promising concept to solve such problems. CAI has the potential to improve spark ignition (SI) engine fuel economy while at the same time solving the trade-off of NOx-soot emissions found in compression ignition (CI) engines. The CAI engine can reach a fuel economy comparable to that of a conventional diesel engine with ultra-low NOx and negligible soot emissions. However, controlling auto-ignition remains the biggest difficulty that hinders the implementation of CAI as a commercial engine. Research towards a cleaner and more efficient engine is driven by the progressively stringent emission regulation imposed worldwide. Therefore, the CAI was developed to meet the emissions target while maintaining engine performance. CAI works on the principle of lean mixture and auto-ignition. To obtain CAI combustion, the temperatures in the cylinder must be sufficient to initiate auto-ignition. Without the use of a spark plug or injector, the CAI suffers from a direct control mechanism to start the combustion. The most practical approach to controlling the initiation of auto-ignition in CAI is diluting the intake charge by either trapping the residual gas or recirculating the exhaust gas. Both approaches enable the engine to achieve CAI combustion without requiring significant modifications to control the onset of CAI combustion phase.